Effect of Chloride‐Based Accelerator in the Presence of Water‐Reducing and Retarding Admixture on Autogenous Shrinkage. Issue 6 (23rd March 2016) - Shanahan, Natallia; Buidens, Daniel; Riding, Kyle; Zayed, A.
Abstract : Rapid repair concrete mixtures commonly used for full‐depth concrete pavement repair sections can use large dosages of accelerating admixtures to increase strength gain rates and decrease the time to traffic opening. Most often, these mixtures also contain water‐reducing and retarding admixtures (WRRAs) to allow for the use of a low water–cementitious material ratio in order to meet strength requirements. The use of large dosages of accelerating admixtures in combination with retarding admixtures could have significant side effects on concrete. Autogenous shrinkage of low water–cementitious concrete can contribute to high tensile stresses and cracking problems. The effect of calcium chloride‐based accelerating admixture dosage, when used with WRRAs, on autogenous shrinkage was measured. It was found that the inclusion of calcium chloride‐containing accelerating admixtures has a nonlinear effect on the pore size distribution and consequently a nonlinear increase on the autogenous shrinkage.